PENGARUH KUALITAS KEHIDUPAN KERJA, KOMITMENPEGAWAI DAN MOTIVASI KERJA TERHADAP KEPUASANKERJA PEGAWAI DI KEMENTERIAN INVESTASI - Oki Rahmatna Tiba (2022)
Based on a survey conducted to employees to measure the level of job satisfaction during the Covid-19 pandemic, there was a decrease in job satisfaction. Reducing job satisfaction can be indicated by the number of employees who resign or move to other agencies. The purpose of this study is to investigate and demonstrate whether there is a relationship between job happiness and the quality of one's work life, employee commitment, and work motivation. This research method is descriptive quantitative with a sample of 86 respondents from the Ministry of Investment/BKPM employees. The descriptive and inferential data analysis techniques were utilized in conjunction with the SmartPLS version 3.2.7 analysis tool to produce the results. As a result of the findings, quality of life had an effect on job satisfaction, employee commitment had an effect on job satisfaction, and work motivation had no effect on job satisfaction.